Effect of shoulder to pin diameter ratio on mechanical and microstructural properties of friction stir welded magnesium alloy AZ31B - Nurul Hidayah, Othman (2018)
Weight reduction in automotive and aircraft industries is a main concern in improving fuel economy and reducing environmental pollutions. Recently, magnesium alloys are constantly gaining importance as lightweight structural materials for automotive applications. Conventional fusion welding methods for joining magnesium alloys produce some defects such as porosity and hot crack, which deteriorate their mechanical properties. Friction stir welding (FSW) is capable of joining magnesium alloys without melting, and thus, it can eliminate problems related to solidification. This research focuses on the effect of shoulder to pin diameter ratio on friction stir welding of magnesium alloy AZ31. Two pieces of AZ31 alloy with thickness of 2 mm were friction stir welded by using conventional milling machine. The shoulder to pin diameter ratio used in this experiment are 2.25, 2.5, 2.75, 3, 3.33, 3.66, 4.5, 5 and 5.5. The rotational speed and welding speed used in this study are 1000 rpm and 100 mm/min respectively. This experiment was conducted according to the design of experiment by using the central composite design (CCD) from a response surface method (RSM). Mechanical properties of FSW AZ31B were evaluated by using a tensile and hardness test. Based on the ultimate tensile strength (UTS) results, mathematical model was developed together with a parameter optimization. Metallurgical analyses were conducted using an optical microscope, and scanning electron microscope (SEM). Result stated that highest UTS at shoulder to pin ratio of 3.33 with 241.391 MPa and weld efficiency of 91 % from based metal. The lowest tensile strength was at shoulder to pin ratio of 5.5 with 158.11 MPa and weld efficiency of 60 % from based metal. According to statistical analysis, the most influenced parameter was the pin diameter (PD) followed by the shoulder diameter (SD). The mathematical model was developed with accuracy up to 0.034% standard deviation error. The accuracy of optimized parameter by comparing the prediction and experimental was 0.46% with tensile strength 243.10 MPa and weld efficiency of 92 % from based metal at shoulder to pin ratio 3.1. Equiaxed grains were observed at the thermomechanically effected zone (TMAZ) and stir zone (SZ) indicating fully plastic deformation. The grain size of stir zone increased with decreasing shoulder to pin ratio from ratio 3.1 to 5.5 due to higher heat input. The heat affected zone (HAZ) grain size at higher tensile strength is 10.234 μm while HAZ grain size at lowest tensile strength is 54.31 μm. It is observed that, surface galling and faying surface defect is produced when excessive heat input is applied. It was found that SZ hardness at ratio 3.1 is higher than SZ at ratio 5.5 that are 90.97HV and 71.73HV respectively. In conclusion, the magnesium alloy AZ31B was successfully welded by using friction stir welding. Shoulder to pin diameter ratio give effect to the mechanical and microstructural properties of AZ31B FSW. The optimum shoulder to pin ratio shows higher tensile strength with fine and equiaxed grain size that indicate higher hardness.